Pelatihan Penulisan dengan Metode Imla’ di Ponpes As-Sunniyyah Jember - M. Abdul Ghofur; Chainun A’ini (An-Nuqthah, 2022)
Arabic writing skills must be in accordance with writing procedures such as using the imla 'method with its qaidah. The second grade students of ibtidaiyah madrasah Assunniyyah in writing Arabic lack the correct Arabic writing skills, such as connecting hijaiyah letters. This study aimed to make students able to write Arabic writing in accordance with the correct qaidah. The assisted method used was community development which was focused on training the imla' method. The imla' method maked it easy for students to write Arabic writing that is in accordance with the rules of Arabic writing and students could also express the ideas that are in their minds and put them into written form and hone their skills in terms of remembering words. Writing training is needed in order to minimize student errors in writing Arabic.